Graphene oxide and gold nanoparticles-based dual amplification method for immunomagnetic beads-derived ELISA of parvalbumin. (April 2020) - Wang, Yanbo; Qi, Qinqin; Zhou, Jinru; Li, Huan; Fu, Linglin
Abstract: Fish has been recognized as one of the "Big-Eight" allergenic food sources with parvalbumin (PV) being one of the major allergens. Here, we report a novel immunomagnetic beads-derived enzyme-linked immunosorbent assay (ELISA) method which employs antibody functionalized graphene oxide (GO) and gold nanoparticles (AuNPs) to amplify the detection signal of PV. The GO and AuNPs are modified with monoclonal antibody (mAb) and HRP-labeled secondary antibody respectively to detect the PV captured by amino-functionalized magnetic beads. With the amplification effect of the antibody modified GO and AuNPs, the proposed ELISA could selectively detect PV with a detection limit as low as 4.29 ng/mL when using pure PV. Moreover, the recovery rates are found to range from 89.82% to 115.37% in the spiked samples. The feasibility in real-world fish sample analysis further shows that the proposed immunomagnetic beads-derived ELISA is a highly promising approach for PV detection and pave a new way for food safety analysis. Highlights: A dual amplified ELISA by antibody functionalized GO and AuNPs for PV detection. A simple method with good sensitivity, specificity and reproducibility. Promising detection potential for four real-world fish samples.